Relative Weight Analysis of the Western Aphasia Battery. Issue 10 (3rd October 2021) - Ellis, Charles; Peach, Richard K.; Rothermich, Kathrin
ABSTRACT: Background: The Western Aphasia Battery (WAB) is one of the most widely used batteries for assessing people with aphasia. Despite longstanding use, it is unclear how the individual components of the battery contribute to the aphasia quotient (AQ), which profiles aphasia severity. Objectives: The primary objective of this study was to explore the individual contributions of the four major components (Spontaneous Speech, Auditory Verbal Comprehension, Repetition, Naming) and the 10 subtests of the WAB to the WAB AQ using relative weight analysis (RWA). The second objective was to evaluate whether the contributions that these components and subtests make to the WAB AQ are influenced by aphasia type (fluent vs non-fluent). Methods & Procedures: Data for 288 persons with aphasia obtained from the AphasiaBank were analyzed in this study. RWA was performed with the R relaimpo package 2.2–3 using WAB AQ scores, scores from the major components, and scores from the10 subtests that are used to calculate the AQ. A second RWA was completed to examine whether the relative weights for these measures vary as a function of aphasia type (fluent vs non-fluent). Outcomes & Results: Results of RWA for the four major components of the AQ indicated that Spontaneous Speech contributes 30%, Auditory Verbal Comprehension 20%, Repetition 25%, and Naming/Word Finding 25% to the AQ. RWA for the 10 WAB subtests revealed the major contributors to be Fluency (14.4%), Repetition (14.1%), Information Content (13.1%), and Object Naming (10.5%). In comparisons of the four major areas between individuals with fluent vs non-fluent aphasia, only the contribution of Spontaneous Speech differed between the two groups with this area contributing 31% to the AQ in those individuals with fluent aphasia and 28% in those with non-fluent aphasia. Conclusions: RWA demonstrated that the major components of the WAB do not contribute equally to the AQ but that the contribution of Spontaneous Speech is less than has been suggested previously. The strongest contributors to the AQ are primarily measures of expressive language. This greater influence of the expressive language measures on the AQ should be considered carefully when interpreting the AQ and aphasia severity.